Effect of Ethanolic Extract of Avocado (Persea americana Mill.) Seed on the Testis Histology (Mus musculus l.) Induced Monosodium Glutamate (MSG) - Yusni Atifah; Dwi Junita Zega; Yuni Ahda; Siska Alicia Farma (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2024)
Monosodium Glutamate (MSG) is a substance that is able to produce free radicals such as ROS (Reactive Oxygen Species), which can cause oxidative stress in the body and damage reproductive organs such as the testes. The purpose of this study was to determine the effect of avocado seed ethanol extract (Persea americana Mill.) on the histology of the testes of mice (Mus musculus L.) induced monosodium glutamate (MSG). This research is an experimental study that was conducted in October 2023 – January 2024 at Biology Laboratory, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang. The design used is a Complete Randomized Design (CRD) with 4 treatments and 6 repeats. The data obtained were analyzed using the ANOVA test (Analysis of variance) using the SPSS 23 application. The results showed that the administration of avocado seed ethanol extract showed a noticeable effect on the diameter of the testes of male mice exposed to MSG. However, it showed no noticeable influence on testicular weight, seminiferous tubule diameter and Leydig cell count. Ethanol extract avocado seed dose 0.84 mg /g body weight / day (P1) was able to improve the diameter of mice testes that had been induced MSGKeyword: Avocado seed extract, Histology of testis, Mice, MSG